The Influence of Knowledge and Economic Status on Early Marriage in Keliling Danau District, Kerinci Regency in 2022 - Sri Astuti Siregar; Aysah Aysah; Marta Butar Butar; Usi Lanita (The International Science of Health Journal, 2024)
According to WHO, early marriage is a marriage between a couple or one of the partners is still categorized as a child or teenager under the age of 19 years. Jambi Province ranks ninth in the rate of marriage at a young age in Indonesia, amounting to 14.8% in 2019, where the percentage for Kerinci Regency is 21%. Among the factors that influence early marriage are low knowledge and economic status. This research aims to determine the influence of knowledge and economic status on early marriage in Keliling Danau district, Kerinci regency. The method used in this research was an analytical survey with a cross-sectional approach where 92 women from couples of childbearing age were the research sample. The sampling technique was simple random sampling and the data was analyzed using chi-square test analysis. Early marriage among respondents was 48.9%, the majority of respondents had good knowledge (65.2%) and high economic status (81.5%). The results of statistical tests show that there is an influence between the knowledge variable (p-value=0.003) and economic status (p-value=0.025) on early marriage. Therefore, it is hoped that regional governments can coordinate across the health sector to increase outreach regarding the prevention of early marriage and the negative impacts it causes.